Metamaterial‐based wideband circularly polarised antenna with rotated V‐shaped metasurface for small satellite applications. Issue 7 (1st April 2019) - Ameen, M.; Chaudhary, R.K.
Abstract : This Letter explains the design and development of a wideband circularly polarised (CP) antenna based on composite metamaterial (MTM) structures which are applicable for use in small satellite applications. The presented antenna is based on a modified co‐planar waveguide feeding technique. The proposed antenna unit cell offers compact size due to its MTM property with dimensions of 0.088λ0 × 0.19λ0 at 2.4 GHz. The CP radiation is obtained by placing two composite right/left‐handed transmission line unit cells orthogonally and exciting two orthogonally‐polarised modes simultaneously. A new 4 × 4 unit cell artificial magnetic conductor metasurface is designed with a compact size at the same operating frequency of MTM‐based CP antenna as a ground plane for the proposed antenna, which is found to be increased bandwidth, improved gain, and wider axial ratio bandwidth without altering the antenna compactness. The final antenna obtains an overall dimension of 0.37λ0 × 0.37λ0 × 0.18λ0 at 2.5 GHz. The measured result shows a wider impedance bandwidth of 860 MHz (33.07%), improved axial ratio bandwidth of 410 MHz (15.92%), and a good gain of 5.76 dBic is obtained which are adequate for the use in modern small satellite applications.